Perbedaan Pola Komunikasi Romantis antara Interaksi Tatap Muka dan Interaksi Melalui Media Sosial - Alissa Agustine; Miftahul Jannah; Endah Nur Aulia; Konto Iskandar Dinata (Journal of Innovative and Creativity, 2025)
The rapid development of digital technology has significantly transformed the way romantic partnerscommunicate. Interactions that were once dominated by face to face communication are now increasinglyfacilitated through social media and instant messaging platforms. This study aims to analyze the differencesbetween romantic communication patterns in face-to-face interactions and those conducted through social media,as well as their implications for relationship quality. This research uses a literature review method by examiningrecent studies published between 2018 - 2024. The findings indicate that face-to-face communication remainscrucial for building intimacy through clear messages and rich nonverbal cues. Meanwhile, digital communicationprovides accessibility and continuous contact, especially for long-distance couples, but it also introduceschallenges such as digital jealousy, miscommunication, and expectations for immediate responses. These resultshighlight the importance of balancing direct and digital communication to maintain harmony, trust, and emotionalstability in modern romantic relationships.